Development of a vibration-damping, sound-insulating, and heat-insulating porous sphere foam system and its application in green buildings - Shi Hua; Moses Oyaro Okello; Jian Zhang (Scientific Reports)
Abstract With the development of green buildings, people pay more attention to the quality of the indoor sound environment. The air sound insulation performance of floors and exterior walls plays a key role in today's green buildings. The thermal performance of the enclosure structure's floor and exterior wall heat transfer resistance is an important factor in reducing building carbon emissions in green buildings. The aim of this paper is to study the efficiency of the acoustic and thermal insulation of a foaming system with porous carbon balls and the combination of different structural ways of construction boards and external walls. The acoustic and thermal parameters of different sound insulation and thermal insulation systems designed with porous carbon sphere foam and inserted into the floors and exterior walls are compared to highlight the optimal structure. The theoretical and experimental tests showed that to improve the sound insulation performance of the floor, a sound insulation system needs to be placed on the surface of the floor in contact with the impact object and inlaid in the vertical gap in contact with the floor and the wall. Furthermore, it has been determined that the surface of the foam particle acoustic ball with micropores has good sound absorption performance. Finally, the high-quality building thermal insulation material with low thermal conductivity in any combination with the floor slabs and the external wall structure improves the thermal insulation performance.